Novel Immunoinformatics Approaches to Design Multi-epitope Subunit Vaccine for Malaria by Investigating Anopheles Salivary Protein - Rajan Kumar Pandey (Nature Portfolio, 2018)
Abstract Malaria fever has been pervasive for quite a while in tropical developing regions causing high morbidity and mortality. The causal organism is a protozoan parasite of genus Plasmodium which spreads to the human host by the bite of hitherto infected female Anopheles mosquito. In the course of biting, a salivary protein of Anopheles helps in blood feeding behavior and having the ability to elicit the host immune response. This study represents a series of immunoinformatics approaches to design multi-epitope subunit vaccine using Anopheles mosquito salivary proteins. Designed subunit vaccine was evaluated for its immunogenicity, allergenicity and physiochemical parameters. To enhance the stability of vaccine protein, disulfide engineering was performed in a region of high mobility. Codon adaptation and in silico cloning was also performed to ensure the higher expression of designed subunit vaccine in E. coli K12 expression system. Finally, molecular docking and simulation study was performed for the vaccine protein and TLR-4 receptor, to determine the binding free energy and complex stability. Moreover, the designed subunit vaccine was found to induce anti-salivary immunity which may have the ability to prevent the entry of Plasmodium sporozoites into the human host.